2022
DOI: 10.1136/bmjopen-2020-048194
|View full text |Cite
|
Sign up to set email alerts
|

Association of mean arterial pressure with 5-year risk of incident diabetes in Chinese adults:a secondary population-based cohort study

Abstract: ObjectiveHypertension predicts the development of diabetes. However, there are still lacking high-quality studies on the correlation between mean arterial pressure (MAP) and incident diabetes. We aimed to explore the relationship between MAP and diabetes in Chinese adults.DesignThis is a secondary retrospective cohort study and the data were downloaded from the ‘DATADRYAD’ database (www.Datadryad.org).ParticipantsThe study included 210 418 adults without diabetes at baseline between 2010 and 2016 across 32 sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In addition, the accuracy of using MAP to predict preeclampsia is better than SBP or DBP alone in early and midtrimester pregnancies (16, 17). Together, these previous studies supported that MAP is sufficiently advantageous in short-term event assessment, and in recent years, MAP has begun to be mentioned in epidemiological studies; several researchers have found MAP to be of good value in assessing the risk of developing various chronic diseases such as atherosclerosis (18), diabetes (19)(20)(21), chronic kidney disease (22,23), and metabolic syndrome (24), as well as in predicting poor prognosis in cardiovascular disease (9,(25)(26)(27)(28). A series of epidemiological evidence further suggested that MAP may be a useful assessment tool for common chronic diseases; however, data on the direction of the association between MAP and the risk of developing NAFLD are still scarce, and it is unclear whether MAP is associated with NAFLD in the general population, whether this association is non-linear, and whether there are differences across populations.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, the accuracy of using MAP to predict preeclampsia is better than SBP or DBP alone in early and midtrimester pregnancies (16, 17). Together, these previous studies supported that MAP is sufficiently advantageous in short-term event assessment, and in recent years, MAP has begun to be mentioned in epidemiological studies; several researchers have found MAP to be of good value in assessing the risk of developing various chronic diseases such as atherosclerosis (18), diabetes (19)(20)(21), chronic kidney disease (22,23), and metabolic syndrome (24), as well as in predicting poor prognosis in cardiovascular disease (9,(25)(26)(27)(28). A series of epidemiological evidence further suggested that MAP may be a useful assessment tool for common chronic diseases; however, data on the direction of the association between MAP and the risk of developing NAFLD are still scarce, and it is unclear whether MAP is associated with NAFLD in the general population, whether this association is non-linear, and whether there are differences across populations.…”
Section: Introductionmentioning
confidence: 70%
“…The occurrence of this result is understandable in our opinion, because when age increases beyond 60 years, there is a gradual decrease in cardiac and vascular compliance and an increase in arterial wall stiffness, followed by a significant decrease in DBP (39,40). While MAP is a composite of SBP and DBP, calculated as 1/3SBP + 2/3DBP (19), it can be seen that the contribution of DBP to the composition of MAP is greater. When DBP decreases significantly in older adults, MAP will also decrease significantly, and subsequently, MAP-related NAFLD risk is lower in data performance than in young and middle-aged populations.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Lee et al [44] revealed a signi cant association between the TyG index and new-onset hypertension speci cally in females. Wu et al [45] established a positive correlation between MAP and diabetes in females. Furthermore, additional research [46] suggests that estrogens-related pathways may play a role, emphasizing the importance of conducting subgroup analyses considering menopause in the study.…”
Section: Discussionmentioning
confidence: 98%
“…For survivors of myocardial infarction, studies showed that maintaining MAP above 80 was important for improving adverse outcomes ( 47 ). Additionally, recent epidemiological surveys have proposed gender-specific MAP thresholds for predicting metabolic syndrome in the elderly at 84 mmHg (male) and 83.3 mmHg (female) ( 48 ), a MAP threshold of 92.833 mmHg for predicting diabetes ( 49 ), and 88 mmHg (male) and 89 mmHg (female) for predicting non-obese NAFLD ( 34 ). In our current study, based on general health examination population data, we found the threshold for identifying NAFLD using MAP to be 88.75 mmHg.…”
Section: Discussionmentioning
confidence: 99%